Systematic and biostratigraphic significance of a chinchillid rodent from the Pliocene of eastern Argentina - Rasia, Luciano Luis (2013)
Two species of chinchillid rodents, Lagostomus (Lagostomopsis) incisus and “Lagostomus (Lagostomopsis) spicatus”, have been recorded from the Monte Hermoso Formation (Montehermosan–Lower Chapadmalalan, Early Pliocene) of southern Buenos Aires Province, eastern Argentina. L. (L.) incisus is based on skull remains,while “L. (L.) spicatus” is based on mandible remains and fragmentary skulls. Detailed study of specimens recovered from the upper section of the Monte Hermoso Formation, from the Irene “Formation”, and the Chapadmalal Formation (late Early–early Late Pliocene, Buenos Aires Province), some of them represented by associated skull and mandible remains, indicates that L. (L.) incisus and “L. (L.) spicatus” are synonymous, with the valid name being L. (L.) incisus. The differences between both nominal species are here attributed to different ontogenetic states and sexual dimorphism. The stratigraphic provenance of the fossil material of L. (L.) incisus indicates a temporal distribution of this species restricted to theMontehermosan?–Chapadmalalan (Early–early Late Pliocene), instead of the Montehermosan (Early Pliocene).